Preface for CEEPE 2020 Proceedings - Caetano, Nídia (2022)
The 3rd International Conference on Energy, Electrical, and Power Engineering (CEEPE) was planned to be held in April 24-26, 2020, in Chongqing, China, and was co-sponsored by the University of Electronic Science and Technology of China; Wuhan University, China; Shandong University, China; South Asia Institute of Science and Engineering (SAISE) and IEEE PES Chongqing Chapter.